Synthesis of Fe₃O₄-Zno-Bentonite Composite and Their Activities in Photodegradation of Methylene Blue - Amanah, Siti Nazilatul; Udaibah, Wirda; Kholidah, Kholidah (Walisongo Journal of Chemistry, 2024)
The development of Fe₃O₄-ZnO-Bentonite photocatalyst material is crucial for the treatment of dye effluents, particularly in response to the rapid growth of the textile industry. Methylene blue, widely used as a textile dye, poses environmental challenges. The combination of bentonite, ZnO, and Fe₃O₄ was synthesized using the coprecipitation method to create a material capable of photodegrading methylene blue dye. Fe₃O₄-ZnO-Bentonite was synthesized using 2 g of bentonite, 8.19 g of Zn(NO₃)₂·6H₂O, and FeSO₄:FeCl₃ weight ratios (in grams) of 4.170:4.055 (composite 1), 4.170:8.109 (composite 2), and 4.170:12.164 (composite 3). Characterization of the photocatalyst materials was conducted using X-ray diffraction (XRD), ultraviolet diffuse reflectance spectroscopy (UV-DRS), and scanning electron microscopy-energy dispersive X-ray (SEM-EDX) mapping. The Fe₃O₄-ZnO-Bentonite composite exhibited a crystalline structure, with band gap values of 2.94 eV (composite 1), 2.07 eV (composite 2), and 2.20 eV (composite 3). The morphology of the material was characterized by small and irregularly shaped chunks. Elemental analysis detected Fe, Zn, and Si peaks, confirming the even distribution of Fe₃O₄ and ZnO within the bentonite matrix. The synthesized Fe₃O₄-ZnO-Bentonite composite demonstrated enhanced photodegradation activity for methylene blue compared to the starting materials. Composite 3 exhibited the highest photocatalytic activity, achieving a degradation efficiency of 96.02% at a methylene blue concentration of 20 ppm (pH 9) within 60 minutes.